The Effect of Cognitive Behavioral Therapy on Sexual Function in Infertile Women: A Randomized Controlled Clinical Trial. Issue 7 (3rd October 2019) - Sahraeian, Maryam; Lotfi, Razieh; Qorbani, Mostafa; Faramarzi, Mahbobeh; Dinpajooh, Fatemeh; Ramezani Tehrani, Fahimeh
Abstract: Infertility and its consequences can have effects on various aspects of a couple's life and also in their marital relationships. This study aimed to investigate the effect of cognitive behavioral therapy (CBT) on sexual function in infertile women. The participants included 52 infertile women randomly assigned to intervention and control groups. A group-based, six-session sexual counseling using a CBT approach was also performed for the intervention group. Sexual functions of the participants in both groups were then assessed via the Female Sexual Function Index (FSFI) at three points in time. The findings revealed no statistically significant difference in the baseline FSFI mean scores of both groups. A significant difference was also reported for FSFI mean scores in the intervention group (29.35 ± 2.71) in comparison with those in the control group (25.84 ± 2.52) ( p < 0.001) one month after intervention, with an effect size of 0.32. The mean scores of all the sexual-function domains, including sexual desire ( p < 0.001), arousal ( p < 0.001), lubrication ( p < 0.001), orgasm ( p < 0.001), satisfaction ( p < 0.001), and pain ( p < 0.001), among the participants in the intervention group had also significantly increased following CBT implementation. The results of this study could be used to promote sexual health in infertile women.